IT happened in India : the story of pantaloons, Big Bazar, Central and the great Indian consumer - Biyani Kishore (Rupa & co., New Delhi, 2009)
Marathi
UGC XIth Five Year Plan 2009-2010
ENGLISH
Keywords: IT happened in India : the story of pantaloons, Big Bazar, Central and the great Indian consumer; Marathi; Marathi